Alley cropping of legumes with grasses as forages : Effect of different grass species and row spacing of gliricidia on the growth and biomass production of forages - Siti Yuhaeni; N.P Suratmini; N.D Purwantari; T Manurung; E Sutedi (Jurnal Ilmu Ternak dan Veteriner, 1998)
A study to evaluate the effect of different grass species and row spacing of gliricidia (Gliricidia sepium) on the growth and biomass production of forages in an alley cropping system was conducted in two different agroclimatical zones i.e. Bogor, located at 500 m a .s .l . with an average annual rainfall of 3,112 nun/year and Sukabumi located at 900 m a .s .l . with an average annual rainfall of 1,402 mm/year . Both locations have low N, P, and K content and the soil is classified as acidic. The experimental design used was a split plot design with 3 replicates . The main plots were different grass species i.e. king grass  (Pennisetum purpureum x P. typhoides) and elephant grass (P. purpureum). The sub plots were the row spacing of gliricidia at 2, 3, 4, 6 m (1 hedgerows) and 4 m (2 hedgerows). The results indicated that the growth and biomass production of grasses were significantly affected (P<0 .05) by the treatments in Bogor. The highest biomass productions was obtained from the 2 m row spacing which gave the highest dry matter production of grasses (1 .65 kg/hill) and gliricidia (0 .086 kg/tree) . In Sukabumi the growth and biomass production of grasses and gliricidia were also significantly affected by the treatments . The highest dry matter production was obtained with 2 m row spacing (dry matter of grasses and gliricidia were 1 .12 kg/hill and 0 .026 kg/tree, respectively) . The result further indicated that biomass production of forages increased with the increase in gliricidia population. The alley cropping system wich is suitable for Bogor was the 2 m row spacing of gliricidia intercropped with either king or elephant grass and for  Sukabumi 2 and 4 m (2 rows of gliricidia) row spacing intercropped with king or elephant grass .   Keywords : Alley cropping, grasses, legumes, row spacing